If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + -19 = 6x + -7 Reorder the terms: -19 + 24x = 6x + -7 Reorder the terms: -19 + 24x = -7 + 6x Solving -19 + 24x = -7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -19 + 24x + -6x = -7 + 6x + -6x Combine like terms: 24x + -6x = 18x -19 + 18x = -7 + 6x + -6x Combine like terms: 6x + -6x = 0 -19 + 18x = -7 + 0 -19 + 18x = -7 Add '19' to each side of the equation. -19 + 19 + 18x = -7 + 19 Combine like terms: -19 + 19 = 0 0 + 18x = -7 + 19 18x = -7 + 19 Combine like terms: -7 + 19 = 12 18x = 12 Divide each side by '18'. x = 0.6666666667 Simplifying x = 0.6666666667
| 2x-3=x^2+3x-7 | | 3+2h=3+5h | | .3-(.9+9k)= | | -5u=-6u-9 | | 9x-2x+66=9x+32 | | 9-77Y=32 | | (9*3-5)+15*2=x | | -5=-6u-9 | | -4p=24 | | 39x+16=39x+80 | | 5xy+2x= | | 100*t=6.5916 | | 0.6n=-6 | | 6x^2+8xy-14y^2=0 | | d=9.1cm | | -9-2t=-3t | | 5(k-4)-4(k+2)-14=-33 | | 3x+8y+66=360 | | 2log(1+3x)=6 | | 9-2t=3t | | 16y-32= | | 4[(5-1)3-(-4)]-53= | | 2(3x+2y)-3(x+y)= | | 4x^3+2x^2+12x+6=0 | | 4x^3+2x^2+12+-6=0 | | 4(n+7)-2(n+3)=-15n | | 4a-6+6a= | | 9x-(6x+2)=9x-50 | | 2n+3=-5 | | 18x+4y=44 | | 40=7.5*x | | (7x-3)+(11y+5)+x=180 |